Optimalitas Perancangan Website: Pendekatan User Centered Design untuk Pengalaman Pengguna Berbagai Usia di Situs Jalan Cantik - Nugroho, Ardra Maulana Adwitiya; Suprihadi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
In the digital age, a deep understanding of user experience (UX) and user interface (UI) is crucial for enhancing user satisfaction. This research explores the application of User Centered Design (UCD) in designing the "Jalan Cantik" website. By understanding the preferences, needs, and abilities of users from various age groups, the aim is to create a website that is more engaging, user-friendly, and effective in facilitating public participation in road infrastructure maintenance. The study also assesses the usability of the "Jalan Cantik" website using the System Usability Scale (SUS) with 50 respondents of different ages. The results show an average SUS score of 80.25, which falls into the "Excellent" category based on the SUS adjective rating scale. This score reflects a high level of user satisfaction, particularly in ease of navigation, information clarity, response speed, and design consistency.